2020
DOI: 10.3390/brainsci10090576
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill Exercise Buffers Behavioral Alterations Related to Ethanol Binge-Drinking in Adolescent Mice

Abstract: The binge-drinking pattern of EtOH consumption, which is frequently observed in adolescents, is known to induce several neurobehavioral alterations, but protection strategies against these impairments remain scarcely explored. We aimed to study the protective role of treadmill physical exercise on the deficits caused after repeated cycles of binge-like EtOH exposure in the cognition, motivation, exploration, and emotion of C57BL/6J mice from adolescence to adulthood. Animals were divided into four groups: cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 63 publications
1
10
1
Order By: Relevance
“…The results clearly indicate that cognitive function in AIE rats was impaired compared to the control mice. Consistent with our results, previous studies have shown that heavy alcohol exposure in adolescence could lead to a deficit in adult cognitive performance, reflected by other behavioral tests, including Y-maze [ 31 ], Morris water maze [ 32 , 33 ], radial arm water maze, Hebb-Williams maze and tube dominance test [ 34 ]. Moreover, the 8-week treadmill exercise intervention significantly decreased the number of working memory errors on day 2 and decreased the time needed to finish the test on day 1, day 2, day 3 and day 4 of the acquisition session in the eight-arm radial maze test.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results clearly indicate that cognitive function in AIE rats was impaired compared to the control mice. Consistent with our results, previous studies have shown that heavy alcohol exposure in adolescence could lead to a deficit in adult cognitive performance, reflected by other behavioral tests, including Y-maze [ 31 ], Morris water maze [ 32 , 33 ], radial arm water maze, Hebb-Williams maze and tube dominance test [ 34 ]. Moreover, the 8-week treadmill exercise intervention significantly decreased the number of working memory errors on day 2 and decreased the time needed to finish the test on day 1, day 2, day 3 and day 4 of the acquisition session in the eight-arm radial maze test.…”
Section: Discussionsupporting
confidence: 92%
“…These results seem to be consistent with other research which found wheel running and survival-enhancing environmental complexity in adolescence-attenuated alcohol exposure induced deficits in hippocampus-dependent learning and memory, including trace eyeblink conditioning and conditioned fear to the context [ 24 ]. However, some inconsistent results of no rescue in cognitive performance after regular aerobic exercise has been found in AIE models [ 31 , 35 ]. Inconsistent results may be due to many different factors such as AIE models, exercise types, exercise intensity and duration and stages of abuse process.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, some of the emotional and cognitive alterations found were maintained into adulthood, even during a long period of abstinence, suggesting the need for interventions at an early age to avoid later alcohol dependence. In this sense, previous studies of our group have found a positive effect from aerobic exercise and cognitive training, which are valuable strategies to counteract some behavioural alterations associated with ethanol intake during adolescence and early adulthood 44,51 …”
Section: Discussionmentioning
confidence: 85%
“…Unfortunately, some of the emotional and cognitive alterations found were maintained into adulthood, even during a long period of abstinence, suggesting the need for interventions at an early age to avoid later alcohol dependence. In this sense, previous studies of our group have found a positive effect from aerobic exercise and cognitive training, which are valuable strategies to counteract some behavioural alterations associated with ethanol intake during adolescence and early adulthood [44, 51].…”
Section: Discussionmentioning
confidence: 95%
“…The behavioural tests (Fig.1) were performed based on previously published protocols from days 56-62 for mice in late adolescence and from days 78-84 for animals in adulthood [44, 45]. This behavioural battery of tests allowed the assessment of exploratory activity, anxiety-related behaviours and cognitive domains in the animals.…”
Section: Methodsmentioning
confidence: 99%